Influence of Content Marketing, Live Streaming, Reviews, and Beauty Vloggers on Scarlett Whitening Purchases - Rolani, Mita; Haryanto, Totok; Purwidianti, Wida; Miftahudin, Muchamad Agung (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to determine the effect of content marketing, live streaming, customer reviews, and beauty vloggers on the decision to purchase Scarlett Whitening on TikTok Shop. The population in this study were active students from all faculties at Muhammadiyah University Purwokerto who had used Scarlett Whitening. The sampling technique used was purposive sampling, resulting in a total of 144 respondents in this study . The research analysis test used Structural Equation Modeling (SEM) as the data analysis technique, utilizing SmartPLS software version 3.0. The results of the study indicate that content marketing, beauty vloggers, and online customer reviews have a positive and significant influence on purchasing decisions, demonstrating the importance of informative, persuasive, and credible digital content in shaping consumer behavior on TikTok Shop. Conversely, live streaming does not show a significant effect on purchasing decisions, suggesting that its effectiveness may depend on execution quality or audience engagement levels. These findings imply that Scarlett Whitening should prioritize strengthening content marketing strategies, collaborating with credible beauty vloggers, and encouraging positive customer reviews to enhance consumer trust and purchase intentions, while reevaluating and optimizing live streaming approaches to improve their impact on purchasing decisions.